Past and future adaptation pathways. (1st January 2016) - Fazey, Ioan; Wise, Russell M.; Lyon, Christopher; Câmpeanu, Claudia; Moug, Peter; Davies, Tammy E.
Abstract : Adaptation pathways are increasingly being used as a foresight tool to help guide the implementation of climate change adaptation and deliberate transformation. This paper applies a pathways lens as a hindsight tool to provide new understanding about past change and adaptation relevant for improving future adaptation pathways approaches. Four case studies of past adaptations to change are examined: Solomon Islands Communities, Canadian forest-dependent communities, a Transylvanian village, and responses to climate adaptation policies in Australia. The results highlight that responses to change in these diverse case studies involve complex transitions that gradually create new conditions and trajectories; manifest as multiple but inter-related pathways of change and response at different social or spatial scales (e.g. different paths for different households or communities); have legacies and continuities across time that affect future pathways of change; are affected by power in complex ways; and can create further change and need for adaptation. Analyses also highlight that when working with prospective adaptation approaches as a response to climate change there is a need to consider: (1) underlying assumptions, values and principles associated with the future; (2) the existence of inter-connected multiple pathways and their implications for reinforcing existing social inequalities; and (3) how understanding past change provides inspiration for new and transformative futures. Overall, the paper concludes that shifts towards analyses for change rather than simply about change, such as adaptation pathways, will require more careful consideration of underlying ontological assumptions about the relationships between past, present and future.